Ruthless - Hancock, Anne Mette, 1979- (Hancock, Anne Mette, 1979- Kaldan and Scháfer mystery, 2023)
"When Jan Frischof, a dying elderly man, gives a deathbed confession too unbelievable to be true, journalist Heloise Kaldan immediately knows there's a deeper story to uncover. Her gut soon proves to be right--Jan immediately backtracks and warns her that they will both be in danger if she asks any more questions. Could this kind and elderly man really be a cold-blooded killer? Heloise quickly realizes that this is a darker, and far more complicated, investigation. Jan is clearly afraid of something, but who or what he's afraid of could be a dangerous question for Heloise to find the answer to. As she digs deeper, Heloise begins to see that Jan's confession is connected to a string decades-old disappearances. But next of kin and police are lying to her at every turn, and she has no idea what else Jan could be hiding. Enlisting her friend, detective inspector Erik Sch̃fer, Heloise begins her descent into the past, unsure of what she will unearth" --